Gender differences in the progression of metabolic responses during incremental exercise - Kang, J.; Hoffman, J. R.; Chaloupka, E. C.; Ratamess, N. A.; Weiser, P. C. (The Journal of Sports Medicine and Physical Fitness, 2006)
Aim: The present investigation was undertaken to elucidate the differences in the progression of metabolic responses during incremental exercise between men and women of similar maximal aerobic capacity. Methods: Twenty males and 20 females served as subjects for the study. Each subject was randomly assigned to perform a graded exercise test on either a cycle ergometer or a treadmill. Of the 20 subjects within each gender, 10 were tested on the cycle ergometer, whereas the other half was tested on the treadmill. During each test, absolute V.O2, relative V.O2, and HR were recorded during the last 15 seconds of every minute throughout the test. These variables were then plotted separately as a function of work rate so that a best-fit linear regression equation was generated for each of the three plots. Results: Under the cycle condition, we found no difference in slope of increment in absolute V.O2 between genders. However, the slope of increment in relative V.O2 and HR was greater (P<0.05) in women than men. A negative correlation (r=-0.858, P<0.05) was found between body mass and slope of increment in relative V.O2 in men and women combined. Under the treadmill condition, the slope for absolute V.O2 were greater (P<0.05) in men than women. However, in terms of relative V.O2 and HR, no between-gender differences were observed in the slope of increment. A positive correlation (r=0.769, P<0.05) was found between body mass and slope of increment in absolute V.O2 in men and women combined. Conclusion: These results indicate that the progression of metabolic responses during incremental exercise differs between men and women despite a similar fitness. These gender differences may be further attributed to body mass that seems to play a distinctive role when the incremental exercise is conducted on a cycle ergometer and treadmill.